TEKNOLOGI PEMBUATAN TELUR ASIN DENGAN PENERAPAN METODE TEKANAN OSMOTIK - Irawati Ramli; Nurhikmah Wahab (JURNAL ILTEK, 2020)
ABSTRACTThe technology that produces salted eggs is generally a simple technology. differences in the production process and quality of salted egg products are determined based on the processing method. The aim of this study salted eggs can be made in a short time through manipulation of osmotic pressure factors, soaking eggs in vinegar can open the semipermeable membrane on the egg shell so that the salt solution quickly enters in eggs. The research method is first to select duck eggs with good quality, then clean them, prepare a solution of acetic acid with a concentration of 5%, 10%, 15%, 20%, and 25%. Then soak the eggs in a solution of acetic acid with time variations of 5,10,15 and 20 minutes. then wrap the eggs with red rock powder dough, put the egg packages into the heating device for 3 hours with a temperature of 60oC, clean the duck eggs, the last process is the SNI test and the organoleptic test.From this research, the results obtained for the salt content with a short soaking time (5 minutes) and the concentration of 15% acetic acid soaking solution had met the SNI 4277.1996 standard, namely a minimum of 2%. In this case, the soaking process of eggs using acetic acid functions to open the pores of the egg shells so that the oscillic salt process is faster. The results showed that the higher the concentration of acetic acid and the longer the immersion time, the salt osmosis rate was getting faster and the salt content in the eggs was getting higher, and with the osmotic pressure factor manipulation method salted eggs can be made in a short time namely 3 hours.